New electrode material integrates silver nanoprisms with phosphorus-doped carbon nanotubes for forensic detection of nitrite. (20th December 2022) - Promsuwan, Kiattisak; Saichanapan, Jenjira; Soleh, Asamee; Saisahas, Kasrin; Samoson, Kritsada; Phua, Cheng Ho; Wangchuk, Sangay; Kanatharana, Proespichaya; Thavarungkul, Panote; Limbut, Warakorn
Highlights: The proposed nanohybrid was synthesized for the first time. An electrode modified with the nanohybrid detected nitrite in gun shot residue. A portable flow injection detection system was custom built by 3D printing. Nitrite in gunshot residue was successfully quantified. Abstract: A screen-printed carbon electrode (SPCE) was modified with a nanohybrid of silver (Ag) nanoprisms and phosphorus (P)-doped carbon nanotubes (AgNPr@P-CNT). The modified SPCE was coupled with a simple, portable flow system to produce an efficient amperometric sensor for the detection of nitrite ion (NO2 − ). P-doped CNTs were prepared via a one-pot solvothermal method and the P-CNTs were decorated with Ag nanoprisms synthesized by a one-pot chemical reduction method. The as-prepared AgNPr@P-CNT nanohybrid was thoroughly characterized. Energy-dispersive x-ray (EDX) analysis, Fourier transform infra‐red (FTIR), and Raman spectroscopy results confirmed the successful doping of CNTs with P atoms. Transmission electron microscopy (TEM) revealed the decoration of P-CNTs with triangular Ag nanoprisms measuring 25 ± 7 nm. In the optimal condition, the flow injection-amperometric sensor based on the developed AgNPr@P-CNT/SPCE exhibited suitable electrocatalytic activity toward NO2 − oxidation. As a result, NO2 − was detected with high sensitivity (0.73 µA µM −1 cm −2 ), a wide linear range (0.010–4000 µM), and a low limit of detection (0.0032 µM). The proposed sensing system was successfully applied to detect NO2 − in gunshot residue samples, achieving good recoveries. The advantages of the proposed AgNPr@P-CNT nanohybrid can be applied in other electrochemical sensing applications. Graphical abstract: Image, graphical abstract